Rifaximin Stability: A Look at UV, IR, HPLC, and Turbidimetry Methods - Kogawa, Ana Carolina [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Aoac Int, 2018)
The study of the stability of medicines is mandated by the International Conference on Harmonization and the World Health Organization. Rifaximin, an antimicrobial marketed in the form of tablets, has no record of stability studies. Thus, the objective of the present work was to investigate the behavior and stability of rifaximin tablets for 6 months under simultaneous conditions of temperature and humidity by UV, IR, HPLC, and turbidimetry techniques. After 6 months of stability study, rifaximin tablets were shown to obey zero-order kinetics when analyzed by physicochemical methods and second-order kinetics when analyzed by a microbiological method. However, the UV method was not suitable for the evaluation of rifaximin. IR, HPLC, and turbidimetry methods can already be used to evaluate the stability of rifaximin tablets. It is important to analyze products with more than one type of method before releasing results mainly in the case of antimicrobial products in which the association of physicochemical and microbiological techniques must be a rule. Rifaximin tablets can be considered stable after 6 months under conditions of 40 +/- 2 degrees C and 75 +/- 5% relative humidity.